HEGEMONI KERAJAAN BANJAR DI SEPANJANG DAS BARITO - Hindarto, Imam (Naditira Widya, 2010)
The Banjarese Sultanate sovereignty stretched across the south coast to the interior of Kalimantan. As an Islamic kingdom that relied on trade, the Banjarese Sultanate hegemony had made impact toward small kingdoms along the Barito River Basin. A number of archaeological and histotical data suggest the important role of the Barito River Basin in supporting the Sultanate of Banjarese existence. Based on such information, it can be inferred that the Barito River Basin act as the main economy buffer and the borderline of the Banjarnese Sultanate territorial region. In the long run, the Banjarese Sultanate hegemony over the Barito River Basin motivate the growth of a new identity within the political identity commonly known as Urang Banjar